Happiness and Utility : Essays Presented to Frederick Rosen - Philp, Mark; Varouxakis, Georgios, 1966-; Rosen, F. (Book collections on Project MUSE., 2019)
Experts and utility brings together experts on utilitarianism to explore the concept of happiness within the utilitarian tradition, situating it in earlier eighteenth-century thinkers and working through some of its developments at the end of the nineteenth and beginning of the twentieth centuries. Drawing on a range of philosophical and historical approaches to the study of the central idea of utilitarianism, the chapters provide a rich set of insights into a founding component of ethics and modern political and economic thought, as well as political and economic practice. In doing so, the chapters examine the multiple dimensions of utilitarianism and the contested interprpetations of this standard for judgement in morality and public policy. The chapters are written in celebration of the career of Professor Frederick Rosen. They follow his work by concentrating on Bentham and the two Mills, and by the subtleties and sophistication of their understanding of one of the most alluring but elusive ideas of modern times. The volume will be of interest not only to admirers of Rosen but to academics and postgraduate students in disciplines such as Philosophy, Political Theory, History of Political Thought, Legal Theory and Legal History.--